Determining the Prognostic Validity of the Unilateral Horizontal Cyclic Jumps Test in Sprint Performance - Vesna Babić; Ivan Milinović; Marko Čule; Aleš Dolenec (Applied Sciences, 2021)
In sports practice, motor tests are commonly used to predict success in specific segments of sprint running, as well as post-injury tests in rehabilitation. The purpose of this analytical cross-sectional study was to determine the prognostic validity of the unilateral horizontal cyclic jumps for a 20 m (UHCJ20m) test on sprint running success. A sample of 118 kinesiology students aged 20.5 ± 1.2 years with an average height of 179.7 ± 6.4 cm and a body mass of 75.6 ± 7.3 kg was used to determine the correlation between the results of the UHCJ20m test and the results of the 20 m sprint start run (MRLS20m), the 20 m sprint flying start run (MRFS20m), and the 100 m run (M100m). The results showed a moderate correlation in all tests (MRLS20m (R = 0.49), MRFS20m (R = 0.53), and M100m (R = 0.38)) with UHCJ20m. In addition to the final result, the multiple regression analysis showed a significant moderate correlation between the kinematic parameters of the UHCJ20m test and the results in the MRLS20m (R = 0.38), MRFS20m (R = 0.49), and M100m (R = 0.37) tests. The stride length (SL) and the contact time (CT) of the UHCJ20m test were statistically significant predictors for the 100 m sprint, the number of steps for MRLS20m, and the SL and the CT for MRFS20m sprint success. Unilateral horizontal cyclic jumps are a significant predictor of success in sprint running, especially for the maximal speed running segment.